Colloidal Pen Lithography. Issue 5 (6th October 2014) - Xue, Mianqi; Cai, Xiaojing; Chen, Ghenfu
<x xml:space="preserve">Abstract</x> Colloidal pen lithography, a low‐cost, high‐throughput scanning probe contact printing method, has been developed, which is based on self‐assembled colloidal arrays embedded in a soft elastomeric stamp. Patterned protein arrays are demonstrated using this method, with a feature size ranging from 100 nm to several micrometers. A brief study into the specificity reorganization of protein gives evidence for the feasibility of this method for writing protein chips. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>